Patient fibroblast circadian rhythms predict lithium sensitivity in bipolar disorder - Sanghani, HR; Jagannath, A; Humberstone, T; Ebrahimjee, F; Thomas, JM; Churchill, GC; Cipriani, A; Attenburrow, M-J; Perestenko, OV; Cowley, SA; Cader, MZ; Peirson, SN; et al. (Springer Nature, 2020)
Bipolar disorder is a chronic neuropsychiatric condition associated with mood instability, where patients present significant sleep and circadian rhythm abnormalities. Currently, the pathophysiology of bipolar disorder remains elusive, but treatment with lithium continues as the benchmark pharmacotherapy, functioning as a potent mood stabilizer in most, but not all patients. Lithium is well documented to induce period lengthening and amplitude enhancement of the circadian clock. Based on this, we sought to investigate whether lithium differentially impacts circadian rhythms in bipolar patient cell lines and crucially if lithium’s effect on the clock is fundamental to its mood-stabilizing effects. We analyzed the circadian rhythms of bipolar patient-derived fibroblasts (n = 39) and their responses to lithium and three further chronomodulators. Here we show, relative to controls (n = 23), patients exhibited a wider distribution of circadian period (p < 0.05), and that patients with longer periods were medicated with a wider range of drugs, suggesting lower effectiveness of lithium. In agreement, patient fibroblasts with longer periods displayed muted circadian responses to lithium as well as to other chronomodulators that phenocopy lithium. These results show that lithium differentially impacts the circadian system in a patient-specific manner and its effect is dependent on the patient’s circadian phenotype. We also found that lithium-induced behavioral changes in mice were phenocopied by modulation of the circadian system with drugs that target the clock, and that a dysfunctional clock ablates this response. Thus, chronomodulatory compounds offer a promising route to a novel treatment paradigm. These findings, upon larger-scale validation, could facilitate the implementation of a personalized approach for mood stabilization.